Jo Labanyi. Spanish Culture from Romanticism to the Present: Structures of Feeling. Legenda, 2019. - Wadda C Rios-Font (Studies in 20th & 21st Century Literature, 2022)
Review of Jo Labanyi. Spanish Culture from Romanticism to the Present: Structures of Feeling. Legenda, 2019. 349 pp.
Keywords: Spain; culture; romanticism; feeling; emotion; realism